Miami-Dade County’s Urban Forests and Their Ecosystem Services - Francisco Escobedo; Joy Klein; Micah Pace; Henry Mayer; Sebastian Varela (EDIS, 2011)
The urban forest in Miami-Dade County reduces air pollution, controls stormwater, reduces crime, increases real estate values, and improves livability. This 10-page fact sheet can be used by urban foresters, residents, and planners to better understand and maximize the benefits of this important natural resource. Written by Francisco Escobedo, Joy Klein, Micah Pace, Henry Mayer, and Sebastian Varela, and published by the UF Department of School of Forest Resources and Conservation, July 2011. (UF/IFAS Photo by Eric Zamora)